Effect of 8-week n-3 fatty-acid supplementation on oxidative stress and inflammation in middle- and long-distance running athletes: a pilot study - Buonocore, D.; Verri, M.; Giolitto, A.; Doria, E.; Ghitti, M.; Dossena, M. (Journal of the International Society of Sports Nutrition, 2020)
Background: Long-chain n-3 polyunsaturated fatty acids, such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), may alter oxidative status and immune function after exercise. The aim of this pilot study was to determine the probable association between n-3 supplementation and physical exercise, observing the variations in markers of oxidative stress and inflammation. Methods: Thirty-nine subjects of both sexes aged 17-30 years were divided into two groups: 1) (n = 21) trained Athletes; 2) (n = 18) Sedentary subjects. All subjects were given about 4 g/day of n-3 supplementation, rich in EPA and DHA, for 8 weeks. Blood, saliva and urine samples were collected pre- (T0) and post- (T1) supplementation. Hematological parameters (tryglicerides, total cholesterol, HDL, CPK, LDH, HGH, IGF-1), oxidative markers (MDA, 8-OHdG, PCc), antioxidant parameters (GPx, SOD, CAT, DPPH scavenger), exercise-induced stress markers (testosterone and cortisol) and an inflammatory marker (TNF-a) were measured. All tests were two-sided and a p-value of less than 0.05 was considered as statistically significant. Results: The results showed that MDA and TNF-amean values significantly decreased after supplementation in both Athletes and Sedentary subjects: variation was greater in Athletes than in Sedentary control subjects. Generally, our results suggested that supplementation with n-3 PUFAs created a synergic variation in the parameters from a baseline state (T0) to a treated state after supplementation (T1), in terms of size and modality, which was significantly different in Athletes compared to Sedentary subjects. Conclusion: In conclusion, supplementation with about 4 g/day of n-3 PUFAs, rich in EPA and DHA, for 8 weeks, seemed to be effective in counteracting some parameters involved in oxidative stress and inflammation, induced by acute strenuous physical exercise.